Efficacy of a BVDV subunit vaccine produced in alfalfa transgenic plants - Perez Aguirreburialde, Maria Sol; Gomez, Maria Cristina; Ostachuck, Agustín; Wolman, Federico Javier; Albanesi, Guillermo Luis; Pecora, Andrea; Odeon, Anselmo Carlos; Ardila, Fernando Jorge; Escribano, José M.; Dus Santos, Maria Jose; Wigdorovitz, Andres (Elsevier, 2019)
Bovine viral diarrhea virus (BVDV) is considered an important cause of economic loss within bovine herds worldwide. In Argentina, only the use of inactivated vaccines is allowed, however, the efficacy of inactivated BVDV vaccines is variable due to its low immunogenicity. The use of recombinant subunit vaccines has been proposed as an alternative to overcome this difficulty. Different studies on protection against BVDV infection have focused the E2 protein, supporting its putative use in subunit vaccines. Utilization of transgenic plants expressing recombinant antigens for the formulation of experimental vaccines represents an innovative and cost effective alternative to the classical fermentation systems. The aim of this work was to develop transgenic alfalfa plants (Medicago sativa, L.) expressing a truncated version of the structural protein E2 from BVDV fused to a molecule named APCH, that target to antigen presenting cells (APCH-tE2). The concentration of recombinant APCH-tE2 in alfalfa leaves was 1 μg/g at fresh weight and its expression remained stable after vegetative propagation. A methodology based an aqueous two phases system was standardized for concentration and partial purification of APCH-tE2 from alfalfa. Guinea pigs parentally immunized with leaf extracts developed high titers of neutralizing antibodies. In bovine, the APCH-tE2 subunit vaccine was able to induce BVDV-specific neutralizing antibodies. After challenge, bovines inoculated with 3 μg of APCH-tE2 produced in alfalfa transgenic plants showed complete virological protection.